In search of a warning strategy against exchange-rate attacks: Forecasting tactics using artificial neural networks - A. S. Andreou; G. A. Zombanakis; E. F. Georgopoulos; S. D. Likothanassis (Discrete Dynamics in Nature and Society)
“Heart attacks and devaluations are not predictable and, certainly, are never preannounced”. (The usual remark made by government spokesmen shortly after a domestic currency devaluation has taken place.)